Hubungan Kecerdasan Emosional Dengan Prestasi Belajar Mahasiswa Semester Ii Bimbingan Konseling UIN Ar-Raniry - Fauziah Fauziah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
Emotional Intelligence and Learning Achievement. The purpose of this study was to determine the relationship of emotional intelligence and academic achievement second semester students Guidance konselin UIN Ar-Raniry. This type of research is an analytic description with degrees kecepercayaan 95%. The population is all second level students Major of Counseling is 78 students. These results indicate a significant relationship between emotional intelligence and academic achievement were proved with ap value of 0.001